Sustainable and Equitable Growth in Farmer-led Irrigation in Sub-Saharan Africa: What Will it Take? - Lefore, Nicole; Giordano, Meredith A.; Ringler, Claudia; Barron, Jennie (2019)
The rapid development of farmer-led irrigation is increasing agricultural productivity, incomes, employment and nutrition, but it might well not achieve its full potential. Small-scale irrigators tend to be younger, male and better-off. Women and resource-poor farmers – the majority of farmers in sub-Saharan Africa – are disadvantaged and often excluded from the numerous benefits to be gained from irrigation. Equity in access to water management technologies and practices is constrained by numerous factors, including high investment costs, absence of financial services, poor market integration, inadequate information services, and labour constraints. Lack of institutions for collective management of natural resources, such as water, further restricts access for resource-poor farmers, increasing inequity. In the absence of sustainable natural resources management approaches to agricultural intensification, this situation may become more acute as natural resources become increasingly valuable, and therefore contested. Realising the full potential of farmer-led irrigation requires contextualised policies, institutions and practices to improve equity, markets and sustainability and help ensure that sector growth is inclusive and beneficial.